Marketing de Servicios - HO177 - 202302 - Vizarreta Vilcarromero, Walter Manuel (2023)
It is a Hospitality and Administration program-specific course of a theoretical and practical nature, aimed at six- term students. This course is designed for students to gain an understanding of contemporary marketing practices and philosophies. The students will gain an understanding of marketing processes both in theory and application. The role and importance of marketing will be appraised within the framework of both product manufacturers and service industries. During the semester, students will explore key concepts and functions of marketing and will be asked to apply these to a range of business contexts. On this course students will develop the necessary expertise in marketing to design and execute proficient marketing strategies and tactics improving thus companies and organizations commercial performances. The course seeks to develop following general competencies: Innovative Thinking (level 2) and specific competencies ACPHA: Hospitality Management (level 2).A pre-requisite for this course is: HO165 market research.